2011
DOI: 10.2174/157016111793744797
|View full text |Cite
|
Sign up to set email alerts
|

Ezetimibe and Vascular Endothelial Function

Abstract: Hypercholesterolemia is a major risk factor for cardiovascular diseases that has been managed mostly with 3-hydroxy-3-methyl glutaryl coenzyme A reductase inhibitors (statins) that suppress de novo cholesterol synthesis in the liver. Statins also have beneficial pleiotropic effects on the atherosclerotic process that are independent of their ability to lower lipid values. However, the levels of low-density lipoprotein cholesterol (LDL-C) in most hypercholesterolemic patients at high risk for cardiovascular dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 146 publications
0
2
0
Order By: Relevance
“…Ezetimibe is a pharmacological inhibitor of NPC1L1, a cholesterol transporter that is highly expressed in the apical membrane of enterocytes and the canalicular membrane of hepatocytes. The main mechanism of ezetimibe's beneficial effects is inhibiting intestinal and hepatic cholesterol absorption through NPC1L1, thereby lowering cholesterol 127 . Interestingly, recent studies have shown that ezetimibe could inhibit oxidative stress, urokinase-type plasminogen activator receptor (uPAR) expression, or IL-6 secretion in human umbilical vein endothelial cells (HUVECs) 128,129 , and have direct vasodilatory effects on rat mesenteric resistance arteries 130 .…”
Section: Discussionmentioning
confidence: 99%
“…Ezetimibe is a pharmacological inhibitor of NPC1L1, a cholesterol transporter that is highly expressed in the apical membrane of enterocytes and the canalicular membrane of hepatocytes. The main mechanism of ezetimibe's beneficial effects is inhibiting intestinal and hepatic cholesterol absorption through NPC1L1, thereby lowering cholesterol 127 . Interestingly, recent studies have shown that ezetimibe could inhibit oxidative stress, urokinase-type plasminogen activator receptor (uPAR) expression, or IL-6 secretion in human umbilical vein endothelial cells (HUVECs) 128,129 , and have direct vasodilatory effects on rat mesenteric resistance arteries 130 .…”
Section: Discussionmentioning
confidence: 99%
“…Many studies reported that ezetimibe improves vascular endothelial dysfunction [65][66][67][68] , although whether the effect was as good as 69) , superior to 70) , or weaker than 71,72) the effect of statins is controversial. However, the inhibitory effect of simvastatin on SNA was not observed with ezetimibe 17) .…”
Section: -3 Ezetimibementioning
confidence: 99%
“…340 flow in the circulation. Elevated PV may contribute to tissue damage by impairing microcirculatory flow due to shear stress damage at the blood-endothelial interface [10][11][12][13][14].…”
Section: Cardiovascularmentioning
confidence: 99%